ChemInform Abstract: Evaluation of Achiral Templates with Fluxional Broensted Basic Substituents in Enantioselective Conjugate Additions. Issue 21 (May 2015) - Adachi, Shinya; Takeda, Norihiko; Sibi, Mukund P.
Abstract Efficient Mg‐catalyzed enantioselective addition of malononitrile to pyrazolidinone‐derived enoates (I) is achieved in the presence of indanone‐derived ligand BOX.